Functional Brain Connectivity of Language Functions in Children Revealed by EEG and MEG: A Systematic Review - Gaudet, Isabelle; Hüsser, Alejandra; Vannasing, Phetsamone; Gallagher, Anne (Frontiers in Human Neuroscience, 2020)
The development of language functions is of great interest to neuroscientists, because these functions count among the fundamental capacities of human cognition. For many years, researchers aimed at identifying cerebral correlates of language abilities. More recently, the development of new data analysis tools has generated a shift towards the investigation of complex cerebral networks. In 2015, Weiss-Croft and Baldeweg published a very interesting systematic review on the development of functional language networks, explored through the use of fMRI. Compared to fMRI, and due to their excellent temporal resolution, MEG and EEG provide different and important information on brain activity. Both therefore constitute crucial neuroimaging techniques for the investigation of the maturation of functional language brain networks. The main objective of this systematic review is to provide a state of knowledge on the investigation of language-related cerebral networks in children, through the use of EEG and MEG, as well as a detailed portrait of relevant MEG and EEG data analysis methods used in that specific research context. To do so, we have summarized the results, and systematically compared the methodological approach of 24 peer-reviewed EEG or MEG scientific studies that included healthy children and children with or at high-risk for language disabilities, aged from birth up to 18 years of age. All included studies employed functional and effective connectivity measures such as Coherence, Phase Locking Value and Phase Slope Index, and did so using different experimental paradigms (e.g. at rest or during language-related tasks). This review will provide more insight into the use of EEG and MEG for the study of language networks in children; contribute to the current state of knowledge on the developmental path of functional connectivity in language networks during childhood and adolescence; and finally allow future studies to choose the most appropriate type of connectivity analysis.